2015
DOI: 10.1017/s1049023x15004872
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Hurricane Shelter Viral Gastroenteritis Outbreak on a Responding Medical Team

Abstract: Medical teams providing shelter care during viral gastroenteritis outbreaks are susceptible to contracting the virus while caring for patients. When responding to similar incidents in the future, teams should not only be ready to implement aggressive infectious control measures but also be prepared to care for team members who become ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Except for the abundance presence of Salmonella typhimurium, no significant changes in pathogens were observed after Hurricane Michael in the Florida panhandle. Our results strengthen findings from previous studies where increase in human cases of infectious diseases were reported in human populations after hurricanes and include viral gastroenteritis and legionellosis in New York [28,29]; nontuberculous mycobacteria after hurricanes in Louisiana, Florida and Oklahoma [30]; cholera in Haiti [31] and E. coli, Giardia, Cryptosporidium in New Orleans [5]. The results presented in this study, while only from two locations, are indicative of the comprehensive need for development of pathogenic libraries along the entire US coastal regions.…”
Section: Discussionsupporting
confidence: 91%
“…Except for the abundance presence of Salmonella typhimurium, no significant changes in pathogens were observed after Hurricane Michael in the Florida panhandle. Our results strengthen findings from previous studies where increase in human cases of infectious diseases were reported in human populations after hurricanes and include viral gastroenteritis and legionellosis in New York [28,29]; nontuberculous mycobacteria after hurricanes in Louisiana, Florida and Oklahoma [30]; cholera in Haiti [31] and E. coli, Giardia, Cryptosporidium in New Orleans [5]. The results presented in this study, while only from two locations, are indicative of the comprehensive need for development of pathogenic libraries along the entire US coastal regions.…”
Section: Discussionsupporting
confidence: 91%
“…Personal protective equipment (PPE) is essential in protecting employees from zoonotic diseases and in avoiding disease spread to other animals and premises (1,2,3,4,5,6). Personal protective equipment ranks the lowest on the hierarchy of controls against occupational hazards, which includes elimination (removing the hazard), substitution (replacing the hazard), engineering controls (isolation from the hazard), and administrative controls (protocols to minimise the hazard) (7).…”
Section: Introductionmentioning
confidence: 99%